PARP-14 Promotes Survival of Mammalian α but Not β Pancreatic Cells Following Cytokine Treatment - D'Angeli, Floriana; Scalia, Marina; Cirnigliaro, Matilde; Satriano, Cristina; Barresi, Vincenza; Musso, Nicolò; Trovato-Salinaro, Angela; Barbagallo, Davide; Ragusa, Marco; Di Pietro, Cinzia; Purrello, Michele; Spina-Purrello, Vittoria (Frontiers in Endocrinology, 2019)
PARP-14 (poly-ADP Ribose Polymerase-14), a member of the PARP family, belongs to the group of Bal proteins (B Aggressive Lymphoma). PARP-14 has recently appeared to be involved in the transduction pathway mediated by JNKs (c Jun N terminal Kinases), among which JNK2 promotes cancer cell survival. Several pharmacological PARP inhibitors are currently used as antitumor agents, even though they have also proved to be effective in many inflammatory diseases. Cytokine release from immune system cells characterizes many autoimmune inflammatory disorders, including type I diabetes, in which the inflammatory state causes β cell loss. Nevertheless, growing evidence supports a concomitant implication of glucagon secreting α cells in type I diabetes progression. Here, we provide evidence on the activation of a survival pathway, mediated by PARP-14, in pancreatic α cells, following treatment of αTC1.6 glucagonoma and βTC1 insulinoma cell lines with a cytokine cocktail: interleukin 1 beta (IL-1β), interferon gamma (IFN-γ) and tumor necrosis factor alpha (TNF-α). Through qPCR, western blot and confocal analysis, we demonstrated higher expression levels of PARP-14 in αTC1.6 cells with respect to βTC1 cells under inflammatory stimuli. By cytofluorimetric and caspase-3 assays, we showed the higher resistance of α cells, compared to β cells, to apoptosis induced by cytokines. Furthermore, the ability of PJ-34 to modulate the expression of the proteins involved in the survival pathway suggests a protective role of PARP-14. These data shed light on a poorly characterized function of PARP-14 in αTC1.6 cells in inflammatory contexts, widening the potential pharmacological applications of PARP inhibitors.